Fast and clean functionalization of MWCNTs by DBD plasma and its influence on mechanical properties of C–epoxy composites. Issue 77 (22nd August 2015) - Krushnamurty, K.; Srikanth, I.; Rao, G. H.; Prasad, P. S. R.; Ghosal, P.; Subrahmanyam, Ch.
<x xml:space="preserve">Abstract</x> TPD profile of various MWCNTs samples before and after air plasma treatment: (a) CO2 evolution, (b) CO evolution.